The Aesthetics of Resistance, Volume II : A Novel, Volume 2 - Weiss, Peter, 1916-1982 (Book collections on Project MUSE., 2020)
Regarded by many as one of the leading works of this century, this novel documents the resistance to fascism in Europe (and within Germany) during WWII.